Debts, deficits, economic recovery, and the US government - Dimitri B. Papadimitriou; Greg Hannsgen (Levy Economics Institute of Bard College, 2010)
In this new brief, President Dimitri B. Papadimitriou and Research Scholar Greg Hannsgen evaluate the current path of fiscal deficits in the United States in the context of government debt and further spending, economic recovery, and unemployment. They are adamant that there is no justification for the belief that cutting spending or raising taxes will reduce the federal deficit, let alone permit solid growth. The worst fears about recent stimulative policies and rapid money-supply growth are proving to be incorrect once again. In the authors' view, we must find the will to reinvigorate government and to maintain Keynesian macro stimulus in the face of ideological opposition and widespread mistrust of government.
Keywords: 330